Part-time working arrangements for managers and professionals: a process approach - Gascoigne, Charlotte (Cranfield University, 2014)
This thesis concerns the relatively recent phenomenon of part-time managers and professionals. The focus is the part-time working arrangement (PTWA) and specifically the process by which it emerges and develops, building on existing literature on working-hours preferences, the role of the organization in part-time working and alternative work organization for temporal flexibility. Two large private-sector organizations, each operating in the UK and the Netherlands, provided four different research sites for narrative interviews with 39 part-time managers and professionals. The key contribution to knowledge is to identify the process of developing a PTWA as a combination of the formal negotiation of a flexibility task i-deal and an informal process of job crafting. In a situation of high constraint – where the individual’s goals conflict with organizational norms and expectations – the tensions between ‘being part-time’ and ‘being professional’ necessitated identity work at each stage, as individuals constructed a ‘provisional self’ which in turn enclosed each stage of the development of the PTWA. The four stages were: first, evaluation of alternative options, including postponing the transition to part- time until more appropriate circumstances arise; secondly, preparation of the individual business case for part-time; thirdly, formal negotiation of a flexibility task i-deal; and finally an informal, unauthorized adaptation of the arrangement over time. Collaborative crafting of working practices (predictability, substitutability, knowledge management) provided greater opportunities for adaptation than individual activities. This study’s contribution to theory in the nascent field of part-time managers and professionals is a process model which suggests how three sets of discourses act as generative mechanisms at each stage of the emergence and development of the PTWA, creating or destroying ‘action spaces’. These discourses are: the perceived ‘nature’ of managerial and professional work, the perception of part-time as a personal lifestyle choice, and the understanding of part-timers as either ‘other’ or the ‘new normal’.
Keywords: Flexible working; temporal flexibility; i-deals; job crafting; identity discourses; provisional selves